1988
DOI: 10.1172/jci113582
|View full text |Cite
|
Sign up to set email alerts
|

Human growth hormone gene and the highly homologous growth hormone variant gene display different splicing patterns.

Abstract: Stably transfected cell lines containing the normal human growth hormone (hGH-N) and human growth hormone-variant (hGH-V) genes have been established in order to study the expression of these two highly homologous genes. Each gene was inserted into a bovine papillomavirus shuttle vector under the transcriptional control of the mouse metallothionein gene promoter and the resultant recombinants were transfected into mouse C127 cells. The transfected cells containing the hGH-N gene secrete two hGH proteins, 91% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 26 publications
0
48
0
1
Order By: Relevance
“…The GH heterogeneity arises from different sources, one of which is the presence of two related genes in the human GH gene cluster with tissue-specific expression: the GH-N gene in the anterior pituitary and the GH-V gene in the placenta (8)(9)(10). The pituitary secretion of GH is pulsatile and regulated mainly by two hypothalamic peptides, GH-releasing hormone (GHRH) and somatostatin (SRIH).…”
Section: Introductionmentioning
confidence: 99%
“…The GH heterogeneity arises from different sources, one of which is the presence of two related genes in the human GH gene cluster with tissue-specific expression: the GH-N gene in the anterior pituitary and the GH-V gene in the placenta (8)(9)(10). The pituitary secretion of GH is pulsatile and regulated mainly by two hypothalamic peptides, GH-releasing hormone (GHRH) and somatostatin (SRIH).…”
Section: Introductionmentioning
confidence: 99%
“…Each of these genes has in common a five-exon structure and each encodes a major secreted protein product of 22-24 kD. Two alternative splicing pathways have been identified in the hGH-related gene transcripts: use ofan alternative splice-acceptor site within exon 3 ofthe hGH-N gene, resulting in the expression of a 20-kD internal deletion form of hGH (6)(7)(8), and the retention of intron 4 in hGH-V transcript resulting in an mRNA (hGH-V2 mRNA) with the potential to encode a novel 26-kD protein (9). The expression of the hGH-N gene is limited to somatotroph cells in the anterior pituitary and the expression of the hCS gene to the syncytiotrophoblastic epithelium of the placenta (10).…”
Section: Introductionmentioning
confidence: 99%
“…The hPrl gene has a wider distribution of expression in vivo including the lactotroph cells ofthe anterior pituitary, the decidual basalis of the placenta (1 1, 12), and decidualized endometrium of the nongravid uterus during days 22-28 of the menstrual cycle (13). The in vivo expression of the hGH-V gene has recently been directly demonstrated by the isolation and sequence analysis of hGH-V and hGH-V2 cDNAs from the placenta (8). A placental growth hormonelike molecule found in maternal sera at increasing concentrations during gestation most likely represents a circulating form ofat least one ofthe hGH-V gene expression products (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviations Nb 2 -GH, GH bioactivity evaluated by Nb 2 cell bioassay PI, ponderal index GA, gestational age hGH, human GH Serum GH is represented mainly by the 22-kD form and by several other monomeric size variants (1,2). The 20-kD variant, which differs from the 22-kD form in that residues 32-46 are deleted (3), is reported to be the second most common circulating isoform (4,5) and is believed to be produced by alternative splicing (6,7). It has recently been shown that the 22-kD and the 20-kD forms are under the pituitary drive in normal and short children and that the serum levels of the 20-kD isoform parallel those of the 22-kD after pharmacologic stimuli as well as during spontaneous secretion (8).…”
mentioning
confidence: 99%